Comparative engine performance of DI pick-up diesel engine tested by mixing metal oxide and bio-solution additives in diesel fuel and palm biodiesel blends(B5) - K. Fangsuwannarak; K. Triratanasirichai (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Applications and Design in Mechanical Engineering 2012 (ICADME 2012) organized by School of Mechatronic Engineering, Universiti Malaysia Perlis (UniMAP), 27th - 28th Februari 2012 at Bayview Beach Resort, Penang, Malaysia.